Bibliometric Analysis of Studies on Glycemic Index, Diabetes, and Rice Consumption - Wati, Devni Nevita; Yuniarti, Elsa (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
The prevalence of type 2 diabetes continues to increase along with the consumption pattern of high glycemic index foods, such as white rice, which triggers a spike in blood glucose. Alternatives such as brown and black rice with a lower glycemic index and high fiber, resistant starch, and antioxidant content are considered better in controlling blood sugar. This study analyzes research trends related to glycemic index, rice types, and diabetes using the VOSviewer-based bibliometric method from Scopus data from 2017–2021. The results show an increase in research on this topic with four main clusters: risks of white rice, metabolic syndrome, benefits of brown and black rice, and nutritional approaches in diabetes prevention. This study confirms the potential of brown and black rice as alternative strategies for diabetes management and opens up opportunities for further research in this field.